Elucidating the multimodal anticancer mechanism of an organometallic terpyridine platinum(II) N-heterocyclic carbene complex against triple-negative breast cancer In Vitro and In Vivo - Zhang, Jing-Jing; Xu, Qi-Jie; Schmidt, Claudia; Abu El Maaty, Mohamed A.; Song, Jinglin; Yu, Chunqiu; Zhou, Jun; Han, Kang; Sun, Hao; Casini, Angela; Ott, Ingo; Wölfl, Stefan (Journal of medicinal chemistry, 2023)
Treatment of triple-negative breast cancer (TNBC) has long been a medical challenge because of the lack of effective therapeutic targets. Targeting lipid, carbohydrate, and nucleotide metabolism pathways has recently been proven as a promising option in view of three heterogeneous metabolic-pathway-based TNBC subtypes. Here, we present a multimodal anticancer platinum(II) complex, named Pt(II)caffeine, with a novel mode of action involving simultaneous mitochondrial damage, inhibition of lipid, carbohydrate, and nucleotide metabolic pathways, and promotion of autophagy. All these biological processes eventually result in a strong suppression of TNBC MDA-MB-231 cell proliferation both in vitro and in vivo. The results indicate that Pt(II)caffeine, influencing cellular metabolism at multiple levels, is a metallodrug with increased potential to overcome the metabolic heterogeneity of TNBC.
Gesehen am 26.04.2023